Hollow microsphere combined with optical harmonic Vernier effect for strain and temperature discrimination. (July 2020) - Gomes, André D.; Ferreira, Marta S.; Bierlich, Jörg; Kobelke, Jens; Rothhardt, Manfred; Bartelt, Hartmut; Frazão, Orlando
Highlights: Combination of optical harmonic Vernier effect with a special strain sensor. Complex Vernier effect case - no reference interferometer is used. The effect allows high strain sensitivities to be achieved. Additional demonstration of simultaneous measurement of strain and temperature. Analysis on the performance of the optical Harmonic Vernier effect in series. Abstract: Achieving a new generation of enhanced sensors requires the development of structures that result from the fusion of different concepts and effects. In this paper, we combine a special strain sensing structure with an optical sensitivity magnification, through harmonics of the Vernier effect. The recently demonstrated harmonics of the Vernier effect result from increasing the optical path length (OPL) of one of two interferometers by multiple times the OPL of the other interferometer. The effect generates higher magnification factors, proportional to the order of the harmonics. The sensing structure is demonstrated for strain and temperature discrimination, allowing compensation for temperature fluctuations. We explore the complex case of the optical Vernier effect in series, where both interferometers are used as sensing interferometers (no reference interferometer is used). Our results also suggest that the magnification enhancement provided by harmonics of the Vernier effect for a configuration in series is the same as for a configuration in parallel: the magnification factor increases proportionally to the order of the harmonics.